Lymphoma of the Sublingual Gland: Clinical, Morphological, Histopathological, and Genetic Characterization - Iversen, Lars; Eriksen, Patrick Rene Gerhard; Andreasen, Simon; Clasen-Linde, Erik; Homøe, Preben; Wessel, Irene; von Buchwald, Christian; Heegaard, Steffen (Frontiers in Surgery, 2020)
Background: Lymphoma of the sublingual gland is rare, representing 1% of all salivary gland lymphomas. In this case report, we present three new cases and compare them to previously published cases, with the aim of characterizing the clinical, morphological, histopathological, and genetic features of this type of malignancy. Materials and Methods: We provide a clinical description of three cases along with a characterization of the microscopic features, including morphology and immunohistochemistry. In addition, we analysed possible cytogenetic rearrangements with the use of fluorescence in situ hybridization (FISH). Results: Case 1: A 61-year-old male presenting with a painless swelling of the floor of the mouth diagnosed as extranodal marginal zone lymphoma (EMZL) of the left sublingual gland. The patient is alive with no evidence of disease after his fourth treatment regimen following several relapses. Case 2: A 68-year-old female with a prior history of mantle cell lymphoma (MCL) presenting with a tender swelling of the left sublingual gland as well as the right submandibular gland. The lesions were diagnosed as relapsing MCL. The patient died of unrelated causes after 18 months of treatment. Case 3: A 75-year-old female presenting with a swelling of the floor of the mouth diagnosed as follicular lymphoma (FL) of the left sublingual gland. The patient received chemotherapy along with radiotherapy and was still alive 10 years after the diagnosis. Conclusion: The three cases of sublingual gland lymphomas presented in this case report resemble lymphomas of other major salivary glands. The clinician should be aware of this type of malignancy and that the clinical presentation may not differ from benign lesions or other more common malignancies in this location.